HPTLC DENSITOMETRIC QUANTIFICATION OF STEROLS IN ETHYL ACETATE EXTRACT OF EICHHORNIA CRASSIPES (MART.) SOLMS - P.JAYANTHI; P.LALITHA (International Journal of Pharma and Bio Sciences, 2014)
Waterhyacinth is one of the fastest growing plants which disrupt the ecological balance. The plant inspite of its obnoxious nature, is a source of various pharmacologically active compounds. Sterols were isolated from the ethyl acetate extract of waterhyacinth and characterized to be a mixture of stigmasterol and β-sitosterol based on UV, IR, 1D and 2D NMR studies. Quantification of the isolated compound in the ethyl acetate extract of waterhyacinth was carried out using High Performance Thin Layer Chromatography. The correlation coefficient obtained for the linearity was 0.9955 for the compound. The amount of sterols were found to be 4.87 mg/100 mg of ethyl acetate extract of waterhyacinth.